A randomized pharmacokinetic-pharmacodynamic evaluation of the potential biosimilar interferon beta-1a product, CinnoVex®. (1st February 2022) - Scheinin, Mika; Lovró, Zsófia; Maadik, Inger-Helen; Suopanki-Lalowski, Jaana; Seyedagha, Seyed Hossein; Azhdarzadeh, Morteza
ABSTRACT: Background: The objective of the trial was to evaluate the bioequivalence of the interferon beta-1a (IFN beta-1a) biosimilar product candidate CinnoVex® with the reference product Avonex® by comparing the pharmacokinetics/pharmacodynamics (PK/PD), safety and immunogenicity of the two products in healthy subjects. Methods: A total of 41 healthy subjects were randomized in a two-stage design to receive single doses of CinnoVex® and Avonex®. The primary PK endpoint was the area under the concentration–time curve from time 0 to the last quantifiable concentration (AUC0–last ). Additional PK parameters, safety and immunogenicity were evaluated as secondary endpoints. The main secondary PD endpoints were the areas under the concentration–time curves from time 0 to 168 hours (AUC0-168h ) of the PD biomarkers. Results: The two products demonstrated similar PK parameters, and the 90% confidence interval (CI) of the primary PK endpoint was within the bioequivalence acceptance limit. No serious adverse events were reported, and all adverse events (AE) were mild or moderate in severity. Anti-drug antibodies were not observed in any of the study participants. Conclusion: This study demonstrated PK/PD bioequivalence between CinnoVex® and Avonex®. The safety and tolerability profiles of both products were similar. Clinical trials registration: EudraCT Number 2016–000139-41